Pengaruh Kompetensi, Disiplin, Dan Stres Kerja Terhadap Kinerja Karyawan Pada Pt.Tolan Tiga Indonesia (Tolan Estate) - Violla Amandha Subakti; Bayu Eko Broto; Rizki Syahputra (Jurnal Mirai Management, 2023)
The purpose of this study was to determine how much influence competence, discipline, and work stress have on employee performance at PT. Tolan Tiga Indonesia (Tolan Estate). This study uses a quantitative approach method. Which the object of this research is all employees of PT.Tolan Tiga Indonesia (Tolan Estate) as many as 427 employees. And samples taken as many as 100 respondents. the results in this study that simultaneously the variable X has an effect on and is significant on the variable Y. The contribution of competence, discipline, work stress to employee performance at PT.Tolan Tiga Indonesia is 43.1% and the remaining 56.9% is from other factors outside the variable researched. The results of statistical test calculations with sig. 0.000. The Fcount value of 25.197 is greater than 2.47 and sig. 0.000